Varieties of capitalism in multinational companies: A comparative study of Volkswagen Slovakia and Kia Motors Slovakia. (January 2021) - Haipeter, Thomas; Jo, Hyung Je
This paper is about industrial relation (IR) strategies and practices in multinational companies (MNCs). It is based on a comparison of these practices in subsidiaries of different MNC within one country. We discuss how far differences and commonalities can be explained by national IR institutions, by company structures and cultures or by the agency of IR actors. In doing so, this will also address the broader question of how far the varieties of capitalism affect what MNCs do abroad and if, and in what way, they adapt to local conditions in terms of IRs and union structures. The paper is based on a case study comparison of two of the biggest automotive companies, Volkswagen and Hyundai, and their production locations in Slovakia. Both companies have different institutional backgrounds in their host countries with different patterns of labour relations, they are internationalized on a growing level and they both have foreign operations in identical countries like in Slovakia, which makes it possible to analyse the effects of institutions, strategies and labour agency by a comparison of establishments. There are two main findings exposing a strong interplay of the factors under scrutiny. First, in both companies, the local IR patterns are strongly shaped by the varieties of institutions at the company headquarters, whereas the IR institutions of the host country are adapted to them; and second, agency plays a growing role as the labour shortage improves the power position of the unions.